862 Medical complexity in children and young people known to a specialist paediatric palliative care service: a narrative review. (17th August 2022) - Fairgrieve, Kirsten; Downie, Jonathan
Abstract : Aims: To conduct a narrative review of medical complexity in the population of children and young people (CYP, 0-18 years) known to specialist paediatric palliative care (SPPC) within a tertiary children's hospital in the United Kingdom. Methods: A narrative review of the health and medical complexity of CYP with life-limiting conditions (LLC) referred to SPPC was conducted between 1 st June-31 st November 2021. Common indices for medical complexity were agreed by the authors (KF and JD), following literature review and consultation with national experts. Data were collected across the following domains; symptom profiles and medications, hospital admissions and specialist teams involved in care, and dependence on medical technologies. Data were collected from a pre-existing dataset created by the SPPC team. Additional information was collected from the patients' files on the electronic patient record system. CYP whose families declined referral to SPPC, or who died before triage were excluded. Microsoft Excel was used to collect and analyse data. A scoring system was developed by the authors to assist quantification of medical complexity. Results: 33 patients were referred to SPPC during the study period. Of these 26 were included; 7 were excluded (2 died prior to triage; 1 declined referral and 4 did not receive input from SPPC). Of the 26 CYP, 50% (n=13) were female, and 50% (n=13) male. The most common primary diagnoses were genetic 31% (n=8), followed by neurological and congenital. 96% (n=25) had been admitted to hospital at least once in the previous 24 months, with the average number of admissions being 4 ( figure 1 ). 58% (n=15) of CYP had been admitted to (Paediatric Intensive Care) PICU in the last 24 months with 27% (n=7) having had multiple PICU admissions. On average, CYP were cared for by 6 specialist teams. The average number of diagnoses (primary and secondary) was 5. 96% (n=25) of the CYP relied on medical technologies long-term. 92% (n=24) of CYP relied on feeding-support, 69% (n=18) relied on respiratory support, and 15% (n=4) were on renal replacement therapy. The average number of routine medications prescribed to this population was 11. Symptoms associated with LLC were recorded. 96% (n=25) of CYP experienced at least one of these symptoms ( figure 2 ). On average, CYP experienced 4 of these symptoms regularly ( figure 2 ). The most common symptoms encountered in this population were sleep disturbance and secretions. We were unable to quantity intensity of the symptoms from patient notes. Domains were scored using a system devised by the authors to quantify complexity; possible scores range from 3-18. 77% (n=20) of the patients scored between 10-13 out of 18, signifying a high level of complexity across all domains. Conclusion: CYP referred to a SPPC service often have high levels of medical complexity, require frequent hospital care and are dependent on medical technologies. The symptom burden in this population is high; with all included children being on multiple medications. This requires SPPC services to have specialist training in navigating the complex health landscape experienced by these children and their families.